2021
DOI: 10.3389/fimmu.2021.738068
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Prognostic and Immunological Analysis of a Six-Gene Signature Associated With Glycolysis and Immune Response in Uveal Melanoma

Abstract: Uveal melanoma (UM) is a subtype of melanoma with poor prognosis. This study aimed to construct a new prognostic gene signature that can be used for survival prediction and risk stratification of UM patients. In this work, transcriptome data from the Molecular Signatures Database were used to identify the cancer hallmarks most relevant to the prognosis of UM patients. Weighted gene co-expression network, univariate least absolute contraction and selection operator (LASSO), and multivariate Cox regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 52 publications
0
28
0
Order By: Relevance
“…Finally, in a recently published study, Jun Liu et al proposed a novel six-gene based signature ( ARPC1B, BTBD6, GUSB, KRTCAP2, RHBDD3 and SLC39A4 ) for survival prediction and risk stratification in UM [ 155 ]. In brief, using the TCGA database, they initially found that glycolysis and immune response were the most relevant hallmarks for UM related survival [ 155 ].…”
Section: Gene Signatures As Novel Prognostic Biomarkers In Uveal Melanomamentioning
confidence: 99%
See 4 more Smart Citations
“…Finally, in a recently published study, Jun Liu et al proposed a novel six-gene based signature ( ARPC1B, BTBD6, GUSB, KRTCAP2, RHBDD3 and SLC39A4 ) for survival prediction and risk stratification in UM [ 155 ]. In brief, using the TCGA database, they initially found that glycolysis and immune response were the most relevant hallmarks for UM related survival [ 155 ].…”
Section: Gene Signatures As Novel Prognostic Biomarkers In Uveal Melanomamentioning
confidence: 99%
“…Finally, in a recently published study, Jun Liu et al proposed a novel six-gene based signature ( ARPC1B, BTBD6, GUSB, KRTCAP2, RHBDD3 and SLC39A4 ) for survival prediction and risk stratification in UM [ 155 ]. In brief, using the TCGA database, they initially found that glycolysis and immune response were the most relevant hallmarks for UM related survival [ 155 ]. Subsequently, they employed WGCNA, Cox regression analyses and a LASSO algorithm to identify significant hub genes related to glycolysis and immune response, which were used to build the risk model to predict OS of UM patients [ 155 ].…”
Section: Gene Signatures As Novel Prognostic Biomarkers In Uveal Melanomamentioning
confidence: 99%
See 3 more Smart Citations